Armstrong, Mary A. and Susan L. Averett. Disparate Measures: The Intersectional Economics of Women in STEM Work - Kahn, Shulamit (Journal of Economic Literature, 2025)
Shulamit Kahn of Boston University reviews “Disparate Measures: The Intersectional Economics of Women in STEM Work” by Mary A. Armstrong and Susan L. Averett. The Econlit abstract of this book begins: “Examines the economic promises of science, technology, engineering, and math (STEM) fields and the viability of those promises, focusing on women from historically disadvantaged populations who work in STEM occupations.”